(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A business foundation is its customers. Marketers need to be very aware of what consumers see, think, like and buy in order to fine-tune their offers and achieve a high level of customer acceptability and contentment. Because rural markets are becoming more and more valuable, marketers are paying closer attention to studying and understanding these regions. Consumer perception is core component of the marketing position. This is a difficult concept to understand, but it is essential to effective marketing. Granite’s inherent attributes, such as its very smooth mirror polish, flawlessly glossy surface, and longevity, have made it known as the “king of monuments”. The most sought- after and extensively stone material in architectural structures and major structural works globally today is Indian granites. Due to its exquisite, aesthetically pleasant characteristics and durability, it enjoys great recognition in the global market. This study looks at the factors that consumer perception and preference to buy granite stones within the research region as well as their purchasing behaviours